The Effect of Problem-Based Learning Model on Mathematical Problem-Solving Ability in Term of Gender Differences of Students - Riyanti, Nur Faddillah; Zetriuslita, Zetriuslita (UNNES JOURNAL, 2025)
The ability to solve mathematical problems is the main objective in mathematics learning, therefore problem-solving should be taught to students as early as possible, practiced, and used not only in mathematics learning, but also in everyday life. TIMSS results indicate that Indonesian eighth-grade students' ability to solve non-routine problems (mathematical problems) is very low, but they perform relatively well in solving factual and procedural problems. This study examined the effect of Problem-Based Learning (PBL) model on mathematical problem-solving ability (MPSA) in terms of gender differences of students in class IX. This research is pseudo-experimental research with non-equivalent control group design. The population in the study were all students of class IX which amounted to 175 students, ranging from class IX.1 to IX.5. The sample in the study was taken by purposive sampling method, so that class IX.4 which amounted to 33 students as the experimental class and class IX.5 which amounted to 33 students as the control class. Data collection techniques were carried out using test techniques with MPSA test instruments in the form of pre-test and post-test. Data analysis techniques used are descriptive analysis and inferential analysis. The results showed that: a) there was a difference in the average MPSA of students in terms of the learning model used (0.000 < 0.05), b) there was a difference in the average MPSA in terms of the gender of students (0.001 < 0.05), and c) there was no interaction between the gender of students and the learning model used on the problem-solving ability used (0.899 > 0.05. It can therefore be concluded that the PBL model has an effect on MPSA when viewed from the perspective of gender differences among students. Abstrak Kemampuan memecahkan masalah matematika merupakan tujuan utama dalam pembelajaran matematika, oleh karena itu pemecahan masalah harus diberikan kepada peserta didik sedini mungkin, dilatih, dan digunakan tidak hanya dalam pembelajaran matematika, tetapi juga dalam kehidupan sehari-hari. Hasil TIMSS menunjukkan bahwa kemampuan peserta didik jenjang SMP kelas dua Indonesia dalam memecahkan masalah non-rutin (masalah matematika) masih sangat rendah. Penelitian ini menguji pengaruh model Problem-Based Learning (PBL) terhadap kemampuan pemecahan masalah matematis (MPSA) ditinjau dari perbedaan jenis kelamin peserta didik kelas IX. Penelitian ini merupakan penelitian eksperimen semu dengan desain kelompok kontrol non-ekuivalen. Populasi dalam penelitian adalah seluruh peserta didik kelas IX yang berjumlah 175 peserta didik, mulai dari kelas IX.1 hingga IX.5. Sampel dalam penelitian diambil dengan metode sampling purposive, sehingga kelas IX.4 yang berjumlah 33 peserta didik sebagai kelas eksperimen dan kelas IX.5 yang berjumlah 33 peserta didik sebagai kelas kontrol. Teknik pengumpulan data dilakukan dengan teknik tes dengan instrumen tes kemampuan pemecahan masalah matematis berupa pre-test dan post-test. Teknik analisis data yang digunakan adalah analisis deskriptif dan analisis inferensial. Hasil penelitian menunjukkan bahwa: a) terdapat perbedaan rata-rata kemampuan pemecahan masalah matematis peserta didik ditinjau dari model pembelajaran yang digunakan (0,000 < 0,05), b) terdapat perbedaan rata-rata kemampuan pemecahan masalah matematis ditinjau dari gender peserta didik (0,001 < 0,05), dan c) tidak terdapat interaksi antara gender peserta didik dengan model pembelajaran yang digunakan terhadap kemampuan pemecahan masalah yang digunakan (0,899 > 0,05). Sehingga dapat disimpulkan bahwa terdapat pengaruh model PBL terhadap kemampuan pemecahan masalah matematis ditinjau dari perbedaan gender peserta didik.